Emergency engineering reconstruction mode based on the perspective of professional donations - Li, Hanyu; Zhang, Xinli; Khaliq, Usama; Rehman, Faheem Ur (Frontiers in Psychology, 2023)
In the construction of emergency engineering, the effective participation of organizations such as government and construction enterprises can improve engineering emergency services to emergency adaptive, which faces the challenge of the enthusiasm of enterprises' emergency participation. This study proposed a new diversified social governance mode for public emergency facility construction. This paper empirically analyzes the performance of stock market returns before and after construction enterprises' participation in emergency engineering. Against the backdrop of covid-19, the analysis based on the sample data of 141 listed companies found that both construction enterprises directly involved in emergency hospital construction and non-state-owned enterprises involved in donations have higher excess return rates. In contrast, social concern has a positive mediating effect between emergency donations and stock market returns. The study suggests that stock market returns from donation behavior and reputation capital become incentives for firms to actively participate in emergency donations, providing a behavioral basis for professional donations by construction firms. Based on the above assumptions, this paper proposes the organizational model of emergency engineering construction and the "Engineering Community" relationship based on the "Engineering Multi-governance" theory. This paper is the first to study the emergency engineering construction model from the perspective of professional donation behavior.